Great American diseases : their effects on the course of North American history - Tizard, Ian R. (Academic Press, 2022)
Great American Diseases: Their Effects on the Course of North American History presents medical history as it pertains to the major infectious diseases of North America. The book is designed to provide an interesting and engaging introduction to microbiology, immunology and epidemiology. With the advent of COVID-19, this book will serve as a reference on the history of previous epidemics. The book presents pandemics in an easy-to-read volume and provides concise chapters on the history of a disease, progression of understanding on the pathogen (agent of the disease), and their social ramifications through the history of North America.